PENGARUH KELENGKAPAN INFORMASI, AKURASI INFORMASI, KEPERCAYAAN STREAMER, DAN STREAMER ATTRACTIVENESS TERHADAP PERCEIVED PERSUASIVENESS YANG DIALAMI PENONTON SHOPEE LIVE - Sholihudin, Nabiila; Surayya Ulfa, Nurist; Setyabudi, Djoko (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
The digital era has brought changes in shopping habits, one of which is the emergence of the new trend of live streaming commerce. In Indonesia, this feature has been met with high enthusiasm, as 86% of online shoppers have claimed to have visited live shopping. Live streaming commerce facilitates real-time interaction between streamers and consumers. Streamers as communicators deliver product persuasion messages and consumers are exposed to information and engage directly with streamer recommendations. Although the streamer's persuasion strategy is relatively the same, the result is different. Consumers do not always make direct purchases according to the persuasion message during live streaming. This study aims to explain the effect of information completeness, information accuracy, streamer trustworthiness, and streamer attractiveness on perceived persuasiveness experienced by Shopee Live viewers using a quantitative approach through a one-shot experimental method. The theory used in this study is the elaboration likelihood model theory, with a purposive sampling technique involving 100 respondents. The results of hypothesis testing with multiple linear regression show that there is no significant effect between information completeness and information accuracy on perceived persuasiveness experienced by respondents when watching Shopee Live. However, streamer trustworthiness and streamer attractiveness are simultaneously proven to affect perceived persuasiveness.